Zastrupitve s psihotropnimi zdravili - Grenc, Damjan (Medicinski razgledi, 2009)
The article deals with the pharmacodynamics, pharmacokinetics, clinical presentation, diagnosis and treatment of selected groups of psychotropic drugs, namely benzodiazepines, monoamin oxidase inhibitors, cyclic antidepressants and second generation serotonergic antidepressants. Epidemiologically speaking, poisonings with benzodiazepines are the commonest type of poisoning among the aforementioned groups in Slovenia. The clinical presentation of benzodiazepine poisoning is usually dominated by a decreased level of consciousness, without cardiovascular or respiratory depression. Poisonings with monoamin oxidase inhibitors show distinct characteristics of adrenergic toxidrome, and the serotonin syndrome is also a possible entity. Poisonings with cyclic antidepressants are the most dramatic from this group of drugs; they present as a combination of anticholinergic toxidrome, cardiovascular depression and/or convulsions. In recent years, poisonings withserotonergic antidepressants are becoming more common epidemiologicallv, with a somewhat less dramatic clinical presentation consisting mainly of central nervous system depression, while respiratory depression is present very rarely. Treatment of poisoning is mainly symptomatic; a specific antidotecan be administered only in benzodiazepine poisoning.
Keywords: Monoaminooksidazni inhibitorji; Psychotropic Drugs; Poisoning; Benzodiazepini; Psihotropna zdravila; Benzodiazepines; Monoamine Oxidase Inhibitors; Antidepresivi; Antidepressive Agents; zastrupitve; zdravila; drug; epidemiologija